Study of the mask-less lithography system and its optimization for high resolution pattern of positive photoresist - Lu, Xiya (Nanyang Technological University, 2024)
The research aim is to investigate the optimal resolution of positive lithographic patterns under the 20x lens and the corresponding experimental parameters based on the DMD-based maskless lithography system. The experimental result is examined carefully with the assistance of SEM to check the accuracy of feature size and the stability of quality. The research also extends to the 100x maskless lithography and makes an effort to explore the limit of resolution. Under the current condition, the completed optimal resolution of the 20x and 100x maskless lithography is 2 and 3 respectively. The procedure of the experiments, analysis of the results, possible constraints of the research experiments, and suggestions for future work are included in the report. The research is meaningful for its effort to explore the resolution capability of maskless lithography, which is a critical parameter of lithography corresponding to the increasing demand for the production of complex and highly integrated structures. It is expected that the result of the research will present a clear and convincing introduction to the resolution capability of high-magnification maskless lithography and support the utilization of such technology in related areas.